2020
DOI: 10.7554/elife.54575
|View full text |Cite
|
Sign up to set email alerts
|

A complex IRES at the 5'-UTR of a viral mRNA assembles a functional 48S complex via an uAUG intermediate

Abstract: Taking control of the cellular apparatus for protein production is a requirement for virus progression. To ensure this control, diverse strategies of cellular mimicry and/or ribosome hijacking have evolved. The initiation stage of translation is especially targeted as it involves multiple steps and the engagement of numerous initiation factors. The use of structured RNA sequences, called Internal Ribosomal Entry Sites (IRES), in viral RNAs is a widespread strategy for the exploitation of eukaryotic initiation.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 81 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…Our results raise the question of which parts of the multi-protein eIF3 complex are responsible for high-affinity binding to specific cellular 5′-UTRs. It is likely that distinct eIF3 surfaces contribute to binding in different cellular 5′-UTRs as shown for two classes of eIF3-binding viral 5′-UTRs (Neupane et al, 2020). Multiple conserved subunits of human eIF3, including a, b, d and g, crosslink directly to cellular mRNA in cultured human cells (Lee et al, 2015), highlighting the potential for distinct subunit binding preferences to contribute to mRNA selection.…”
Section: Discussionmentioning
confidence: 99%
“…Our results raise the question of which parts of the multi-protein eIF3 complex are responsible for high-affinity binding to specific cellular 5′-UTRs. It is likely that distinct eIF3 surfaces contribute to binding in different cellular 5′-UTRs as shown for two classes of eIF3-binding viral 5′-UTRs (Neupane et al, 2020). Multiple conserved subunits of human eIF3, including a, b, d and g, crosslink directly to cellular mRNA in cultured human cells (Lee et al, 2015), highlighting the potential for distinct subunit binding preferences to contribute to mRNA selection.…”
Section: Discussionmentioning
confidence: 99%
“…The 5′ terminal IRES of another member of Dicistroviridae family, the already mentioned virus CrPV, apparently has a distant functional similarity with the HCV IRES, despite differences in their structures. It specifically binds the eIF3 factor, and in this case, this interaction is strictly necessary for the 40S subunit landing [ 152 , 153 ]. Like HCV IRES, the 5′ terminal CrPV IRES interacts with the “optional” ribosomal protein RACK1, which explains the previously found dependence of the translation of the first but not the second CrPV cistron on this protein [ 154 ].…”
Section: Internal Translation Initiationmentioning
confidence: 99%
“…Like HCV IRES, the 5′ terminal CrPV IRES interacts with the “optional” ribosomal protein RACK1, which explains the previously found dependence of the translation of the first but not the second CrPV cistron on this protein [ 154 ]. Nevertheless, detailed structural and functional analysis of the reconstructed complex of this IRES with purified 40S and eIF3 revealed a number of unique features [ 152 ]. Its three domains cover the “head” of the 40S subunit interacting with proteins and rRNA, and the single-stranded region following domain III is loaded into the mRNA channel.…”
Section: Internal Translation Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences have been attributed to eIF3, which is not required by the CrPV IGR IRES. Indeed, in a cryoEM structure of a class III IRES in complex with the 40S ribosomal subunit and eIF3, domain III of the IRES interacted with the eIF3 complex (Hashem et al, 2013; Neupane, Pisareva, Rodriguez, Pisarev, & Fernández, 2020; Siridechadilok, Fraser, Hall, Doudna, & Nogales, 2005). Furthermore, Majzoub et al (2014) showed that loss of the eIF3j subunit, which did not affect cell viability, decreased HCV IRES‐mediated translation.…”
Section: Viruses Exploit the Function Of Specific Ribosomal Proteinsmentioning
confidence: 99%